2016
DOI: 10.1128/aac.01131-16
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Estimation of Tobramycin Exposure in Patients with Cystic Fibrosis

Abstract: cFixed tobramycin (mg/kg) dosing is often inappropriate in patients with cystic fibrosis (CF), as pharmacokinetics are highly variable. The area under the concentration-time curve (AUC) is an exposure metric suited to monitoring in this population. Bayesian strategies to estimate AUC have been available for over 20 years but are not standard practice in the clinical setting. To assess their suitability for use in clinical practice, three AUC estimation methods using limited sampling were compared to measured t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 33 publications
0
38
0
Order By: Relevance
“…Most patients treated with enoxaparin only had one anti‐Xa concentration measured and the estimation of PK parameters, such as clearance, may be less precise than in those who had multiple samples taken. However, it has been shown that the use of one sample when using Bayesian methods is superior than using a standard nomogram and that atypical sampling times can still provide accurate and usable results when using Bayesian methods . Accurate sampling is crucial in all forms of TDM and we recommend that guidelines clearly state optimal sampling times for all drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most patients treated with enoxaparin only had one anti‐Xa concentration measured and the estimation of PK parameters, such as clearance, may be less precise than in those who had multiple samples taken. However, it has been shown that the use of one sample when using Bayesian methods is superior than using a standard nomogram and that atypical sampling times can still provide accurate and usable results when using Bayesian methods . Accurate sampling is crucial in all forms of TDM and we recommend that guidelines clearly state optimal sampling times for all drugs.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that the use of one sample when using Bayesian methods is superior than using a standard nomogram and that atypical sampling times can still provide accurate and usable results when using Bayesian methods. 28 Accurate sampling is crucial in all forms of TDM and we recommend that guidelines clearly state optimal sampling times for all drugs.…”
Section: Limitationsmentioning
confidence: 99%
“…While the log-linear regression method is more commonly used (13), it may be more invasive, tedious, and reactive in nature than Bayesian forecasting. The former requires at least 2 blood sample measurements for predictions (14), whereas Bayesian forecasting may require only 1 sample, and it is not able to give dosage predictions until a dose has first been administered. In adults with febrile neutropenia, a Bayesian approach has been shown to increase the number of patients achieving the desired target exposure to gentamicin compared to the number achieving the desired target obtained when the log-linear regression method is used (15).…”
mentioning
confidence: 99%
“…Even after some three decades of once daily intravenous dosing of tobramycin for acute pulmonary exacerbations, wide variations are still seen in the methods of therapeutic drug monitoring . Until recently, the software programs used in many hospitals to estimate dosing have not been validated . There is a need for the collation of data on the use of CFTR modulators in pregnancy and lactation not only to validate safety, but also because there may be a role for such therapy to prevent the complications of CF that develop in utero , such as meconium ileus, pancreatic insufficiency and congenital absence of the vas deferens.…”
Section: Remaining Challengesmentioning
confidence: 99%
“…36 Until recently, the software programs used in many hospitals to estimate dosing have not been validated. 37 There is a need for the collation of data on the use of CFTR modulators in pregnancy and lactation not only to validate safety, but also because there may be a role for such therapy to prevent the complications of CF that develop in utero, such as meconium ileus, pancreatic insufficiency and congenital absence of the vas deferens. Pharmacists have demonstrated that they can play important clinical, research and cost-saving roles in multidisciplinary CF clinics.…”
Section: Examination Of the Cystic Fibrosis Foundation Drug Developmentmentioning
confidence: 99%